Towards coarse-grained modelling of proteins - Stepanova, M. (Condensed Matter Physics, 2007)
This paper introduces a basic theoretical background to the description of conformational dynamics of proteins
through a system of interacting domains. The essential collective degrees of freedom derived by principal
component analysis of a molecular dynamics trajectory are used as dynamic variables defining the projection
operator technique that underlies the formalism suggested. The explicit form of the corresponding projection
operator is obtained, and the projection method is employed to derive systems of coupled generalized
Langevin equations for both individual atomic degrees of freedom and essential collective degrees of freedom
in a protein. A definition of correlated domains in proteins is introduced based on the analysis of the essential
dynamics. Examples of identification of such domains are presented. A system of coupled generalized
Langevin equations is derived representing the protein through a few interacting domains embedded into a
dissipative medium. Further developments and potential applications of the formalism are outlined. Ця стаття вводить базисну теоретичну основу для опису конформацiйної динамiки протеїнiв через систему взаємодiючих доменiв. Суттєвi колективнi ступенi вiльностi, отриманi аналiзом провiдної компоненти траекторiї молекулярної динамiки, використовуються як динамiчнi змiннi з допомогою технiки проекцiйного оператора, що окреслює запропонований формалiзм. Отримано явну форму вiдповiдного проекцiйного оператора. Проекцiйний метод застосований для встановлення системи зв’язаних узагальнених рiвнянь Ланжевена для iндивiдуальних атомних ступенiв вiльностi та суттєвих колективних ступенiв вiльностi в протеїнi. Визначення кореляцiйних доменiв в протеїнах вводиться на основi аналiзу суттєвої динамiки. Наведенi приклади iдентифiкацiї таких доменiв. Система зв’язаних узагальнених рiвнянь Ланжевена була отримана, шляхом представлення протеїну через кiлька взаємодiючих областей, помiщених в дисипативне середовище. Обговорюються подальший розвиток i можливостi застосування запропонованого формалiзму.